2017
DOI: 10.1016/j.jacl.2017.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bariatric surgery on apolipoprotein C-III levels and lipoprotein distribution in obese human subjects

Abstract: BACKGROUND: Elevated apolipoprotein C-III (apoC-III) has been postulated to contribute to the atherogenic dyslipidemia seen in obesity and insulin-resistant states, mainly by impairing plasma triglyceride-rich lipoprotein (TRL) metabolism. Bariatric surgery is associated with improvements of several obesity-associated metabolic abnormalities, including a reduction in plasma triglycerides (TGs) and an increase in plasma high-density lipoprotein cholesterol (HDL-C).OBJECTIVES: We investigated the specific effect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 62 publications
0
8
0
1
Order By: Relevance
“…In concordance, other studies showed that associated risk factors of cardiovascular disease, hypertension (HTN), type 2 diabetes mellitus (DM), and dyslipidemia, are directly related to higher severity of obesity, mortality, and morbidity [2,6,7]. Bariatric surgery is an effective treatment for morbid obesity, especially with comorbid diseases [2] as it leads to improvement in several cardiovascular risk factors such as DM, HTN, hypertriglyceridemia as well as raising the low HDL cholesterol [2,6]. While some researchers reported improvement in all parameters of the lipid profile after bariatric surgery, other researchers reported that the reduction was only in the levels of LDL cholesterol and serum TG, whereas there were non-significant changes in TC and HDL cholesterol levels [8,9].…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In concordance, other studies showed that associated risk factors of cardiovascular disease, hypertension (HTN), type 2 diabetes mellitus (DM), and dyslipidemia, are directly related to higher severity of obesity, mortality, and morbidity [2,6,7]. Bariatric surgery is an effective treatment for morbid obesity, especially with comorbid diseases [2] as it leads to improvement in several cardiovascular risk factors such as DM, HTN, hypertriglyceridemia as well as raising the low HDL cholesterol [2,6]. While some researchers reported improvement in all parameters of the lipid profile after bariatric surgery, other researchers reported that the reduction was only in the levels of LDL cholesterol and serum TG, whereas there were non-significant changes in TC and HDL cholesterol levels [8,9].…”
Section: Introductionmentioning
confidence: 61%
“…A previous study showed that for every 1 kg body weight loss, serum LDL cholesterol level drops by 0.02 mmol/L, serum TC level drops by 0.05 mmol/L, and serum HDL cholesterol level increases by 0.009 mmol/L [5]. In concordance, other studies showed that associated risk factors of cardiovascular disease, hypertension (HTN), type 2 diabetes mellitus (DM), and dyslipidemia, are directly related to higher severity of obesity, mortality, and morbidity [2,6,7]. Bariatric surgery is an effective treatment for morbid obesity, especially with comorbid diseases [2] as it leads to improvement in several cardiovascular risk factors such as DM, HTN, hypertriglyceridemia as well as raising the low HDL cholesterol [2,6].…”
Section: Introductionmentioning
confidence: 67%
“…Two recent studies have compared the effects on lipid profiles after RYGB and SG: Heffron and coworkers showed a similar weight loss after these two surgical techniques but a higher increase in HDL and ApoA after SG [ 43 ]; on the other hand, Maraninchi and coworkers also showed a similar weight loss after these two surgical techniques, with similar increases in HDL and reductions in triglycerides, but they showed a higher decrease in total cholesterol, LDL and ApoB after RYGB [ 44 ]. Although the effects of bariatric surgery on lipid profiles are clearly beneficial, small differences between surgical techniques need further studies due to small discrepancies which may be due to different selected populations and sample size of studies.…”
Section: Discussionmentioning
confidence: 99%
“…8,36 Weight loss with bariatric surgery is consistently accompanied not only by HbA1c reduction, but has also resulted in markedly reduced plasma triglycerides and apoC-III, and this decrease was accompanied by a redistribution of apoC-III from triglyceride-rich lipoproteins to HDL. 39 However, although tirzepatide resulted in better glucose control and greater weight loss than dulaglutide, the multiple linear regression analysis indicated that tirzepatide-induced weight loss only explained a small portion of the variability in triglycerides.…”
Section: Predictors Of Triglyceride Changesmentioning
confidence: 93%